1996
DOI: 10.1002/(sici)1098-2396(199602)22:2<159::aid-syn8>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

The role of dopamine in epilepsy

Abstract: The clinical benefits of dopamine agonists in the management of epilepsy can be traced back over a century, whilst the introduction of neuroleptics into psychiatry practice 40 years ago witnessed the emergence of fits as a side effect of dopamine receptor blockade. Epidemiologists noticed a reciprocal relationship between the supposed dopaminergic overactivity syndrome of schizophrenia and epilepsy, which came to be regarded as a dopamine underactivity condition. Early pharmacological studies of epilepsy emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
157
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(176 citation statements)
references
References 357 publications
8
157
0
3
Order By: Relevance
“…However, in mice, 5HT loss is milder, while a severe DA depletion occurs, as described in detail by the Colado's group (Colado et al, 2001) and shown by other studies (Stone et al, 1987;Logan et al, 1988;Ali et al, 1991;Cadet et al, 1995;Fornai et al, 2001Fornai et al, , 2004b. Both monoamines might modulate seizures (see, for instance, Pasini et al, 1996;Starr, 1996;Heisler et al, 1998;Torta and Monaco, 2002;Giorgi et al, 2003Giorgi et al, , 2004. However, this is unlikely to occur in the present study.…”
Section: Discussionmentioning
confidence: 81%
“…However, in mice, 5HT loss is milder, while a severe DA depletion occurs, as described in detail by the Colado's group (Colado et al, 2001) and shown by other studies (Stone et al, 1987;Logan et al, 1988;Ali et al, 1991;Cadet et al, 1995;Fornai et al, 2001Fornai et al, , 2004b. Both monoamines might modulate seizures (see, for instance, Pasini et al, 1996;Starr, 1996;Heisler et al, 1998;Torta and Monaco, 2002;Giorgi et al, 2003Giorgi et al, , 2004. However, this is unlikely to occur in the present study.…”
Section: Discussionmentioning
confidence: 81%
“…In 1996, a glutamate-DA interaction proposed by Starr attempted to explain the individual susceptibility to epilepsy in limbic areas (24). According to this hypothesis, in the epileptic brain there is increased tonic excitation of DA neurons by glutamate (Glu) due to the peroxisomal activity on the cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Another important finding is the promotion of seizures observed in patients with no previous history of epilepsy via the use of antipsychotics that act as DA-ergic D2-like antagonists. In contrast, seizure inhibition has been observed when antiparkinsonian drugs, such as pergolide and bromocriptine, which both act by stimulating D2Rs, are administered (24).…”
Section: Resultsmentioning
confidence: 99%
“…The pathophysiology of epilepsy and TS remains unclear, yet abnormal cortico-basal ganglion circuit connections and dopaminergic systems are possibly involved [9]. Alternations of dopaminergic neurotransmission and corticostriatal network are substantially evident in TS.…”
Section: Introductionmentioning
confidence: 99%